Is it possible to diagnose therapeutic adherence in mild cognitive impairment and dementia patients in clinical practice? - Barnestein-Fonseca, Pilar; Guerrero-Pertiñez, Gloria; Gúzman-Parra, Jose; Valera-Moreno, Esperanza; Mayoral-Cleries, Fermín (Frontiers in Pharmacology, 2024)
Non-adherence is common and contributes to adverse health outcomes, reduced quality of life and increased healthcare expenditure. The objective was to assess the diagnostic validity to estimate the prevalence of non-adherence in patients with mild cognitive impairment and dementia using two self-reported methods (SRM) useful and easy in clinical practice, considering the pill count as reference method (RM). Methods: Cohort study nested in Multicenter randomized controlled trial NCT03325699. 387 patients from 8 health centers selected by a non-probabilistic consecutive sampling method. Inclusion criteria:20-28 points MMSE (Mini-Mental State Examination); Older than 55 years; Take prescribed medication and in charge of their own medication use. Followed up for 18 months:baseline, 6, 12 and 18 months. Variables related with treatment adherences were measure in all visits. Variables: age, sex, treatment, comorbidities, MMSE test. Adherence: pills counts and Morisky Green test (MGT) and Batalla test (BT) as SRM. Statically analysis: Descriptive analysis. 95% confidence intervals. Diagnostic validity: 1) open comparison statistical association between SRM and RM; 2)hierarchy comparison: RM as the best method to assess non-adherence, kappa value(k), sensitivity (S), specificity(Sp), likelihood ratio (PPV/PPN). Results: 387 patients were recruited 73.29 (IC95%,72.54- 74.04) years; 59.5% female; Comorbidities: 54.4%HTA, 35.9% osteoarticular pathology, 24.5% DM. MMSE score mean: 25.57 (CI95%, 25.34-25.8). The treatment adherence for RM oscillates between 22.5% in the baseline and 26.3%, 14.8% and 17.9% in the follow-up visits. For SRM the treatment adherence oscillates between 43.5% in the baseline and 32.4%, 21.9% and 20.3% in the follow-up visits. The kappa value was statistically significant in all the comparison in all visits with a score between 0.16-035. About the diagnostic validity, the sensibility oscillated between 0.4 and 0.58, the specificity oscillated between 0.68-0.87 for Morisky-Green Test; sensibility oscillated between 0.4 and 0.7, the specificity oscillated between 0.66-0.9 for Batalla Test; and sensibility oscillated between 0.22 and 0.4, the specificity oscillated between 0.85-0.96 for both tests together. Conclusion: Self-reported methods classify correctly non-adherent subjects. They are very easy and fast for use in the clinical practice, so self-reported methods would be used for the non-adherence diagnosis in patients with mild cognitive impairment and mild dementia.